MicMac strategic variables to reduce pollution in papaya cultivation in Cotaxtla - Villegas-Vilchis, Antonio; Galaviz-Villa, Itzel; Amaro-Espejo, Isabel Araceli; García-Saldaña, Arturo; Toga-Islava, Ana Yesica (Revista Mexicana de Ciencias Agrícolas, 2025)
The municipality of Cotaxtla, Veracruz contributed 50% of the national papaya production, that is, 49 thousand tonnes per year. This production could decrease due to the presence of contaminants in the crops that inhibit the morphological and physiological development of the plant in addition to degrading soil and water. This research aimed to identify: 1) the factors of change involving new phenomena related to the cultivation of papaya (Carica papaya L.) and 2) the strategic variables that characterize the production system in the municipality of Cotaxtla, Veracruz The study was conducted from October 2023 to March 2024 in the municipality of Cotaxtla, Veracruz, and a foresight methodology was used, participatory workshops were held to explore the factors of change and identify the strategic variables that influence decision-making focused on reducing the risks of contamination of the product, soil, and water. The structural analysis or ‘MicMac’ method was used and 44 factors of change and five strategic variables of greater influence and dependence were identified. According to the logical syntax, through adequate training in the management of agrochemicals and their hazardous solid waste and the incorporation of good agricultural practices, the risks of contamination will be reduced, production will be increased, and quality and competitiveness in the market will improve. This knowledge allows us to design actions to reduce the risks of contamination in the papaya cultivation in the municipality of Cotaxtla, Veracruz.